1968
DOI: 10.1111/j.1752-1688.1968.tb02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dye Tracers to Collect Hydrologic Data in Oregon1

Abstract: Dye tracers have been used in Oregon in the Collection of hydrologic data on 2,350 miles of stream channels in the Long Tom, Umpqua, Willmette, and John Day River basins, and in the Carmen‐Smith power tunnel. These investigations demonstrated the usefulness, of dye tracers for determining: (1) estimates of traveltimes and travel rates of water, (2) discharge where standard methods of measuring are not applicable, and (3) dispersion characteristics of streams. Illustrations are used to present the results of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…For the September investigation, stream velocities representing each reach in a downstream direction were 0.27, 0.35, 0.22, and 0.17 ft/s. Velocities in the South Umpqua River from this study and results from a previous study by Harris and Sanderson (1968) are shown in figure 6. The velocities for the earlier high-flow study was controlled by channel friction (Harris and Sanderson, 1968).…”
Section: Time-of-travel Investigationssupporting
confidence: 56%
See 1 more Smart Citation
“…For the September investigation, stream velocities representing each reach in a downstream direction were 0.27, 0.35, 0.22, and 0.17 ft/s. Velocities in the South Umpqua River from this study and results from a previous study by Harris and Sanderson (1968) are shown in figure 6. The velocities for the earlier high-flow study was controlled by channel friction (Harris and Sanderson, 1968).…”
Section: Time-of-travel Investigationssupporting
confidence: 56%
“…1). Stream velocities computed during this study are compared with velocities computed from dye-tracer data collected at higher flows by Harris and Sanderson (1968). Reaeration coefficients computed from field measurements of gas-desorption coefficients are compared with conceptual and semiempirical equations, and new equations were developed for the South Umpqua River between Tiller and Roseburg, Oregon.…”
Section: Purpose and Scopementioning
confidence: 99%
“…A second source of information on the variation of travel times or average velocities through a watershed is from dye tracer studies along river channels. Tests relevant to the problem of spacing of isochrones in flood synthesis have been reported by Harris and Sanderson [ 1968], Carlston [ 1969], and Calkins and Dunne [1970]. These tests have again indicated that average velocity remains fairly constant in a downstream direction.…”
Section: Within Watershedsmentioning
confidence: 95%
“…The Water Resources Division of the Geological Survey performs more time-of-travel dye tracer studies than any other Federal agency, in most cases in cooperation with State and local government agencies (Buchanan, 1964;Harris and Sanderson, 1968;Boning, 1973;Nordin and Sabol, 1974;Hubbard, et aL, 1982). Early tests in the 1960's and 1970's were primarily concerned with evaluating the speed at which the leading edge and peak of a soluble contaminant would move downstream, and in some cases with how long it might persist at some downstream point.…”
Section: Introductionmentioning
confidence: 99%